Cytokine mRNA expression in the mucosa of treated coeliac patients after wheat peptide challenge. (July 1995) - Kontakou, M; Przemioslo, R T; Sturgess, R P; Limb, G A; Ellis, H J; Day, P; Ciclitira, P J
Abstract : This study investigated the presence of mRNA coding for interferon gamma (IFN gamma), tumour necrosis factor alpha (TNF alpha), and interleukins 2 (IL2) and 6 (IL6), in the mucosa of four coeliac patients in remission who had been challenged with either gliadin or synthetic gliadin oligopeptides. Jejunal biopsy specimens from these patients, taken before and at two, four, and six hours after challenge, were hybridised with specific 35S-labelled DNA oligonucleotide probes. The lamina propria of all the patients contained significantly increased numbers of cytokine mRNA expressing cells four hours after challenge with gliadin or an oligopeptide corresponding to amino acids 31-49 of A-gliadin (peptide A). No significant changes were seen with the peptides corresponding to aminoacids 202-220 (peptide B) or 3-21 (peptide C) of A-gliadin, with the exception of one patient who showed a significant increase in the number of TNF alpha mRNA expressing cells four hours after challenge with peptide B. In vivo studies in coeliac disease have shown that significant histological changes occur in the mucosa of treated coeliac patients four hours after challenge with either gliadin or peptide A. These findings suggest that the histological changes seen previously in the mucosa of coeliac patients after wheat peptide challenge may be caused by increased expression of cytokines within the mucosa.